CNPO "3+6", Exploring a New Safety Management and Control Mode for Nuclear Power In-service Inspection. Issue 2 (February 2021) - Wang, Zhulin; Zhang, Liang; Wang, Jiajian
Abstract: CNPO explores a new mode of high-level field management that can cure the root cause from the three basic laws that are easily ignored by the management. By constructing six safety culture systems with the characteristics of nuclear power enterprises, CNPO strives to improve the safety quality of employees in nuclear related enterprises and continuously consolidate the foundation of safety management.